Repeated mechanical damage enhanced Aquilaria sinensis resistance to Heortia vitessoides through jasmonic acid - Chen, Yingying; Liang, Shenghua; Wang, Shuyao; Li, Baocai; Wang, Kun; Zhu, Yongjin; Yang, Risheng; Hao, Xin; Yang, Zhuoying; Shen, Yingbai; Jiang, Rihong; Li, Kaixiang (Frontiers in Plant Science, 2023)
The leaf-chewing pest Heortia vitessoides severely threatens the growth and development of Aquilaria sinensis. Here, we found that mechanical damage (MD) to stem enhanced A. sinensis sapling resistance to H. vitessoides larvae. To reveal the defense mechanisms underlying this observation, we analyzed the types and contents of volatile organic compounds (VOCs), phytohormone contents, and expression of phytohormone-related genes in response to MD and herbivory wounding(HW). We identified several VOCs, such as the pesticides fenobucarb and 2,4-di-tert-butylphenol, in mature leaf (ML) of MD-treated plants. Compared with salicylic acid (SA) or the ethylene (ET) pathway, jasmonic acid (JA) content and JA-related genes were more strongly upregulated. Interestingly, we found a dramatic difference between JA-related upstream and downstream genes expression in YL and ML, which confirmed that JA-Ile accumulation in MD-ML and HW-ML could be derived from local damaged site . Taken together, we provide evidence that the JA pathway plays a dominant role in the A. sinensis response to MD and HW.